2015
DOI: 10.19030/jabr.v31i4.9297
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Disclosures, Information Asymmetry And Stock-Market Liquidity In France

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 56 publications
3
42
0
2
Order By: Relevance
“…They used five proxies for information asymmetry (i.e., quoted spread, effective spread, time-weighted spread, probability of informed trading [PIN] and adjusted PIN) and found negative associations with disclosure for all five proxies. Ajina et al (2015) found statistically-significant negative relationships between both the quoted and the effective bid-ask spread, and their disclosure proxy (voluntary disclosure in annual reports).…”
Section: Price Impactmentioning
confidence: 93%
See 4 more Smart Citations
“…They used five proxies for information asymmetry (i.e., quoted spread, effective spread, time-weighted spread, probability of informed trading [PIN] and adjusted PIN) and found negative associations with disclosure for all five proxies. Ajina et al (2015) found statistically-significant negative relationships between both the quoted and the effective bid-ask spread, and their disclosure proxy (voluntary disclosure in annual reports).…”
Section: Price Impactmentioning
confidence: 93%
“…A number of studies have used different proxies for information asymmetry (e.g. Ajina et al 2015;Fu, Kraft & Zhang 2012;Gajewski & Li 2015;Orens et al 2010). Three are retained here -the quoted or relative bid-ask spread, price impact, and analyst following.…”
Section: Measurement Of Internet Investor Relationsmentioning
confidence: 99%
See 3 more Smart Citations